Monocrystalline Silicon PERC Solar Cell with Rear-Side AlOx Film Formed by Furnace Oxidation - Ching-Hui Hsu; Da-Yao Lao; Likarn Wang (International Journal of Photoenergy)
In this study, AlOx passivation layers on the rear sides of silicon PERC solar cells are formed by thermally oxidizing 3 nm-thick aluminum films deposited in advance by an e-gun evaporator. The oxidation process is conducted in a furnace full of oxygen at 400°C for a duration of 10 minutes, followed by annealing for a duration of 3 minutes at 700°C, and then the stacking of SiNx films on the back surfaces. After that, a second annealing process is done at 400°C for a duration of 10 minutes to repair the defects resulting from the bombardment of ions on the passivation layer. With the thermal oxidation method applied, we confirmed the existence of an AlOx passivation layer with a negative charge density of −3.21×1012 cm-2 for an annealed sample, in contrast to −6.17×1011 cm-2 for an unannealed sample.